2019
DOI: 10.1186/s40580-019-0179-0
|View full text |Cite
|
Sign up to set email alerts
|

Potentiometric performance of flexible pH sensor based on polyaniline nanofiber arrays

Abstract: We report potentiometric performance of a polyaniline nanofiber array-based pH sensor fabricated by combining a dilute chemical polymerization and low-cost and simple screen printing process. The pH sensor had a two-electrode configuration consisting of polyaniline nanofiber array sensing electrode and Ag/AgCl reference electrode. Measurement of electromotive force between sensing and reference electrodes provided various electrochemical properties of pH sensors. The pH sensor show excellent sensor performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(41 citation statements)
references
References 35 publications
0
41
0
Order By: Relevance
“…Figure 4 b is the overpotential corresponding to the curve in Figure 4 a after each stability test. It can be seen that after the stability test, the performance only decreased 6 mV, indicating the good reversibility, which is the better reversibility than the previous work [ 12 , 13 , 31 ].…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…Figure 4 b is the overpotential corresponding to the curve in Figure 4 a after each stability test. It can be seen that after the stability test, the performance only decreased 6 mV, indicating the good reversibility, which is the better reversibility than the previous work [ 12 , 13 , 31 ].…”
Section: Resultsmentioning
confidence: 59%
“…As shown in Figure 3 a, when the pH of the solution is 14, 13.7, 13.4, 13.1, 12.4, 12.1, and 11.4, the overpotentials required to reach a current density of 10 mA cm −2 are 132, 168, 223, 279, 492, 678, and > 1000 mV, respectively. By comparing the overpotential at different pH, it can be found that the overpotential changes significantly with the change of pH which has a higher sensitivity [ 31 , 32 ]. As shown in Figure 3 b, to further analyze the relationship between current density and pH, the required overpotential at a current density of 10 mA cm −2 and different pH values were plotted.…”
Section: Resultsmentioning
confidence: 99%
“…The authors analyzed the sensitivity of the device after sterilization with an autoclave and observed a slight variation that depended on the glass transition of the membrane used as RE. A PANI nanofiber tested in buffer solution led to a superNernstian response (63 mV/pH) [55], whereas a slightly smaller sensitivity was obtained after coating gold interdigitated electrodes with PANI (58.57 mV/pH in the range pH 5.45-8.62, Figure 3B) [56].…”
Section: Potentiometric Ph Sensorsmentioning
confidence: 98%
“…In any case, the sensors should correctly monitor the rate of deterioration of fruit freshness [ 37 ]. An array of concepts for fruit freshness sensors or indicators have been developed including aldehyde [ 38 , 39 ], volatile organic compounds (VOC) [ 40 ], ethanol [ 41 ], hydrogen sulfide (H 2 S) [ 42 ], pH [ 43 , 44 ], and CO 2 [ 45 ]. The sensors or indicators are integrated into the food package as a visible indicator, label, or tag that undergoes color changes according to changes in the freshness markers and/or analytes.…”
Section: Smart Packaging Systems For Fruit Freshnessmentioning
confidence: 99%